G145(P) Review of the management of children with mastoiditis: a single centre experience. (25th October 2020) - Islam, S; Chowdhury, T; Alexander, V; Drysdale, SB
Abstract : Aims: Mastoiditis has an incidence of 8.2/100, 000 hospital admissions, though rare it can cause intracranial complications. The Trust's antibiotic policy recommends co-amoxiclav as first line treatment and ceftriaxone plus metronidazole if there are concerns about concurrent intracranial infection. We aimed to review the diagnostic features, management and outcome of children with acute mastoiditis. Methods: Children receiving antibiotics were identified from the Trust's antimicrobial database. We retrospectively analysed the notes of children admitted between 01/01/17 and 10/05/19 with an initial diagnosis of mastoiditis. We identified 25 patients in whom a diagnosis of acute mastoiditis was made on hospital presentation. We reviewed their notes to identify presenting symptoms, investigations undertaken and medical and surgical management. Results: 25 patients were initially suspected of mastoiditis, diagnosis was confirmed in 16 (64%). Alternative diagnoses included otitis media (n=4, 16%), otitis externa (n=3, 12%), cholesteatoma (n=1, 4%) and pre-auricular lymphadenopathy (n=1, 4%). Patients with a confirmed diagnosis of mastoiditis had a mean (range) age of 4.5 (0.1–12) years and mean (SD) duration of hospitalisation of 3.6 (2.0) days. Post-auricular swelling was seen in 69% (n=11), displacement of pinna in 56% and mastoid erythema in 56% (n=9). 31% (n=5) were treated with antibiotics by their GP prior to admission. Mean CRP on admission was 113.9 (SD 103.4) mg/L and mean white cell count 15.5 × 10 9 /L (SD 4.4 × 10 9 /L). 37% (n=6) had a head CT scan. No patient had confirmed intracranial infection. 69% (n=11) received IV co-amoxiclav as first line management, the remaining 31% (n=5) ceftriaxone and metronidazole. Mean (SD) duration of inpatient antibiotics was 3.6 (2.1) days and outpatient antibiotics 12.7 (9.9) days. 31% (n=5) had surgical intervention; only one (6%) child had positive microbiology ( Streptococcus pneumoniae from pus). 81% (n=13) had an ENT follow up appointment. Conclusion: All patients received a first line antibiotic in line with Trust guidance, although no patients had confirmed intracranial infection. Pus samples did not alter antibiotic choices in this small cohort. This suggests, in our population, most patients can be safely managed with co-amoxiclav as first line therapy.